EDUKASI KESEHATAN MENTAL LANSIA MELALUI SOSIALISASI BERBASIS PENGABDIAN MASYARAKAT - Istiqomah, Istiqomah; Wulandari, Amri; Sulistyowati, Endang Tri; Krismiyati, Murti (LPPM Politeknik Kesehatan Karya Husada Yogyakarta, 2025)
Aging is characterized by various physical, psychological, and social changes that can affect the mental health of older adults. Limited understanding of mental health causes many elderly individuals to perceive psychological complaints as a normal part of aging and not requiring special attention. This community service activity aimed to improve the knowledge and awareness of older adults regarding the importance of maintaining mental health in later life through socialization activities. The method used was health socialization and education with a promotive and preventive approach. The activity was conducted through preparation, implementation, and evaluation stages involving 40 participants aged ≥60 years. Evaluation was carried out using pre-test and post-test questionnaires consisting of 15 multiple-choice questions. The results showed an increase in the average knowledge score from 58.4 in the pre-test to 83.1 in the post-test. In addition, the proportion of participants with a high level of knowledge increased from 20% to 70%. This socialization activity proved effective in improving knowledge, awareness, and motivation of older adults to adopt mentally healthy behaviors. Continuous implementation of similar programs is recommended to support the improvement of quality of life among the elderly.